Targeted Recombination Demonstrates that the Spike Gene of Transmissible Gastroenteritis Coronavirus Is a Determinant of Its Enteric Tropism and Virulence - Sánchez, Carlos M. (American Society for Microbiology (ASM), 1999)
Targeted recombination within the S (spike) gene of transmissible gastroenteritis coronavirus (TGEV) was promoted by passage of helper respiratory virus isolates in cells transfected with a TGEV-derived defective minigenome carrying the S gene from an enteric isolate. The minigenome was efficiently replicated in trans and packaged by the helper virus, leading to the formation of true recombinant and pseudorecombinant viruses containing the S proteins of both enteric and respiratory TGEV strains in their envelopes. The recombinants acquired an enteric tropism, and their analysis showed that they were generated by homologous recombination that implied a double crossover in the S gene resulting in replacement of most of the respiratory, attenuated strain S gene (nucleotides 96 to 3700) by the S gene of the enteric, virulent isolate. The recombinant virus was virulent and rapidly evolved in swine testis cells by the introduction of point mutations and in-phase codon deletions in a domain of the S gene (nucleotides 217 to 665) previously implicated in the tropism of TGEV. The helper virus, with an original respiratory tropism, was also found in the enteric tract, probably because pseudorecombinant viruses carrying the spike proteins from the respiratory strain and the enteric virus in their envelopes were formed. These results demonstrated that a change in the tropism and virulence of TGEV can be engineered by sequence changes in the S gene.